Teacher training and the different educational reforms in Spain: 1960-70 - Beas Miranda, Miguel (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
Different educational reforms depend, among other agents, on the specialists who design them, the politicians who decide them and give them normative and economic support as well as on the teachers who carry them out and whose role has not always been properly considered. Teachers’ activities are determined by their personal attitudes and by the acquisition of competences resulting from their initial and in-service training. The aim of this research is to consider synthetically the initial and in-service training of primary school teachers in the 1960s and 1970s, bearing in mind the Spanish socio-cultural context, the country’s political, nondemocratic centralism and the important reforms of the educational system occurring during those two decades.